The impact of additives applied to the lubricant on the burnishing process and tribological properties - Adamczuk, Krzysztof; Dębowski, Daniel; Wojciechowski, Szymon; Kozak, Dražan; Zabłocki, Miłosz (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this study was to determine the impact of additions of tungsten carbide and silicon carbide microparticles to the lubricant used in the burnishing process on the tribological properties of friction pairs. The cylinders made of AISI 1045 steel constituted a workpiece. Burnishing was made with a lubricant the SN150 base oil with addition of tungsten carbide and silicon carbide microparticles. The tested materials were burnished with forces of 1000 N and 1500 N. Before and after the burnishing process, the surface roughness and hardness of the tested materials were measured.
Keywords: burnishing; lubricants; lubricants additives; friction pairs